Preparing for Graduate-Level Training in Professional Psychology: Comparisons Across Clinical PhD, Counseling PhD, and Clinical PsyD Programs. (October 2016) - Karazsia, Bryan T.; Smith, Lena
In the present study, faculty who teach in clinical and counseling doctor of philosophy (PhD) or doctor of psychology (PsyD) programs completed surveys regarding preferences for prospective student preparations to graduate programs. Faculty expectations of minimum and ideal undergraduate training were highest for scientific methods, though expectations systematically varied among clinical PhD, counseling PhD, and clinical PsyD programs. Faculty preferences for applicants' research and clinical "fit" within the program in which they are applying, as well as general interpersonal skills and intellect, also emerged as important admissions factors. These results describe the desirable undergraduate preparations and qualities of applicants for advanced study in clinical and counseling psychology. The findings have implications for prospective graduate students, faculty who train and mentor undergraduates, and faculty who serve on admissions committees.